Indigenous Practices and Beliefs of Rice Farmers in the Second District of Capiz, Philippines - Magallanes, Jocelyn (JPAIR Multidisciplinary Research, 2020)
People of a long time ago lived in harmony with nature. Because of their dependency on the environment and intimacy with nature, they have come up with a set of beliefs and traditions that becomes the basis of modern rice farming practices. This descriptive study aimed to investigate and document the indigenous practices and beliefs of rice farmers in the second district of Capiz, Philippines. Using the researcher’s made questionnaire and interview schedule, data were gathered from 59 rice farmers. Findings revealed that the majority of the respondents were in their middle age (45-57 years old) and were high school undergraduates. Before planting rice, farmers perform Bungad (planting rice and lemongrass in the corner of the rice field facing east). In planting rice, farmers assure that their stomach is full, the sea is in high tide, and the moon is in progress to the full moon. Another is Gabuo (throwing sliced turmeric while walking around the ripe grains for three consecutive afternoons) to drive away evil spirits. After harvesting, farmers perform pamutang butang or thanksgiving by offering a portion of their best yield to someone they believe mystic. Local farmers utilize mouse traps, dead animals, and plastic strips to get rid of rats, mole cricket, rice bugs, and birds (Maya), respectively. Indigenous practices and beliefs of farmers were based on their forefathers and from their personal observations and experiences. It is recommended that concerned agencies must document farmers’ indigenous beliefs and practices.